PERBEDAAN PEMBERIAN ONGGOK TERFERMENTASI Trichoderma viride TERHADAP PENAMPILAN PRODUKSI AYAM KAMPUNG SUPER (Gallus domesticus sp) - Binti Nur Ajibah; Alfan Setya Winurdana; Eddy Trijana Sudani (Universitas Islam Balitar, 2020)
This research was aimed to determine different use tapioca by product fermentated with Trichoderma viride of Super Native Chicken production which includes Feed Covertion Ratio and Indeks Performance. In this research, used 120 super-native chickens aged 28 days. The method is an experimental with observation techniques. The design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 6 replications. The treatment used in this study P0 (treatment without the addition of tapioca by product fermentated), P1 (treatment with addition of 25% of tapioca by product fermentated), P2 (treatment with addition of 50% of tapioca by product fermentated), P3 (treatment with addition of 75% of tapioca by product fermentated. The results of the research data show that the use of tapioca by product fermentated in Super Native Chicken rations did not have a significant effect (P >0.05) on the Feed Convertion Ratio and Indeks Performance. On the Feed Convertation Ratio with the lowest value in the treatment P0 of 4.17 gr/bird and on the Indeks Performance with the highest value in the treatment P1 of 60.85. The conclusion of this study is the use of tapioca by product fermentated can be given up to 25% in the feed as a substitute